HUMPHRY DAVY NAS PÁGINAS DE PERIÓDICOS BRASILEIROS DO INÍCIO DO SÉCULO XIX - Luiz C. A. Barbosa; Pedro G. M. Gomes; Carlos A. L. Figueiras (Química Nova)
HUMPHRY DAVY ON THE PAGES OF BRAZILIAN EARLY - NINETEENTH CENTURY PUBLICATIONS. Humphry Davy (1778-1829) occupies a singular place in the history of science. His career flourished after the great systematizations carried out at the final decades of the eighteenth century and the early years of the following century. His many discoveries, both of a fundamental as well as of an applied nature, opened numerous pathways in chemistry. This paper aims to show how his research was followed attentively by many in Brazil, at a time when the country was just beginning to establish its very first institutions of higher education and scientific research. It is interesting to see how those new discoveries were avidly followed from a distance and the repercussions they were enjoying at such an early stage in Brazil as an autonomous state.